2014
DOI: 10.1186/s13012-014-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Spreading and sustaining best practices for home care of older adults: a grounded theory study

Abstract: BackgroundImproving health care quality requires effective and timely spread of innovations that support evidence-based practices. However, there is limited rigorous research on the process of spread, factors influencing spread, and models of spread. It is particularly important to study spread within the home care sector given the aging of the population, expansion of home care services internationally, the high proportion of older adult users of home care services, and the vulnerability of this group who are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 43 publications
(64 reference statements)
0
47
0
Order By: Relevance
“…(), Edwards and Grinspun () and Ploeg et al . (), while one document addressed three benefit levers, e.g. UNAIDS and WHO () and one document all four benefit levers (NHS ).…”
Section: Resultsmentioning
confidence: 99%
“…(), Edwards and Grinspun () and Ploeg et al . (), while one document addressed three benefit levers, e.g. UNAIDS and WHO () and one document all four benefit levers (NHS ).…”
Section: Resultsmentioning
confidence: 99%
“…Involve all professions, all departments/programs 3,4,15,19,20,22,30,34 26. Involve patients and families 3,20 27. Support the human dimension through rewards, self-efficacy, engagement/involvement in decision-making 4,6,15 28.…”
Section: Structure and Processesmentioning
confidence: 99%
“…Establish forum for submitting QI ideas from staff, patients, and families (Personal communication, EXTRA Team: Lynda Weaver, MHA, MEd, CE; Isabelle Bossé, BA; Dionne Sinclair, RN, MScN, MCHM, CHE; José Pereira, MBChB, DA, CCFP, MSc) 15. Communicate benefits of improved process to set the stage for spread21,[26][27][28] …”
mentioning
confidence: 99%
“…Grounded theory is often used to help develop theories and in the creation of conceptual models and frameworks from social research, and examples can be found from research in nursing, athletic training, and medicine, as well as other fields. (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) Applying a grounded theory methodology is inductive, in that the researcher begins with no set hypothesis and allows the theory to emerge from the what happened at their table; group dialogue then built upon the previous discussion.…”
Section: Qualitative Research Approachmentioning
confidence: 99%